2022
DOI: 10.3390/diagnostics13010139
|View full text |Cite
|
Sign up to set email alerts
|

Ischiofemoral Impingement Syndrome: Clinical and Imaging/Guidance Issues with Special Focus on Ultrasonography

Abstract: Ischiofemoral impingement syndrome is a neglected cause of posterior hip pain which is derived from narrowing of the space between the lateral aspect of the ischium and the medial aspect of the lesser trochanter. Its diagnosis is challenging and requires the combination of physical tests and imaging studies. In the present narrative review, we found that femoral anteversion predisposes patients to the narrowing of the ischiofemoral space and subsequent quadratus femoris muscle injury. Magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A more recent meta-analysis conducted by Singer et al (24) concluded that a cutoff value of ≤15 mm yielded a sensitivity of 76.9%, specificity of 81.0%, and overall accuracy of 78.3%. Although MRI is the imaging most commonly used to determine the width of the IFS, comparative studies have demonstrated that ultrasound is equivalent to MRI for IFS dimensions (19,25,26). In 2017, the utility of ultrasound for measuring IFS was validated on MRI in 10 asymptomatic patients (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent meta-analysis conducted by Singer et al (24) concluded that a cutoff value of ≤15 mm yielded a sensitivity of 76.9%, specificity of 81.0%, and overall accuracy of 78.3%. Although MRI is the imaging most commonly used to determine the width of the IFS, comparative studies have demonstrated that ultrasound is equivalent to MRI for IFS dimensions (19,25,26). In 2017, the utility of ultrasound for measuring IFS was validated on MRI in 10 asymptomatic patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI is the imaging most commonly used to determine the width of the IFS, comparative studies have demonstrated that ultrasound is equivalent to MRI for IFS dimensions (19,25,26). In 2017, the utility of ultrasound for measuring IFS was validated on MRI in 10 asymptomatic patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…Ischiofemoral impingement syndrome is a neglected cause of posterior hip pain, which originates from narrowing of the space between the lateral aspect of the ischium and the medial aspect of the lesser trochanter [ 85 ]. Femoral anteversion predisposes patients to narrowing of the ischiofemoral space and subsequent quadratus femoris muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pain can originate (proximally) from the tendinous insertion of the hamstring muscles on the ischial tuberosity distal to its myotendinous junction [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…6), the ischiofemoral space can be visualized (▶ Table 2). [15] At this level, dynamic sonographic scanning can be performed to observe in real time how the ischiofemoral space changes its shape/dimension during the different motions and what happens to the anatomical structures located inside (▶ Video 3) [3]. Indeed, in patients with a clinical scenario suspected of ischiofemoral impingement, a peculiar sonographic finding has been described in the pertinent literature.…”
Section: Ischiofemoral Spacementioning
confidence: 99%